Girl gone missing - Rendon, Marcie R. (Rendon, Marcie R. Cash Blackbear mystery, 2021)
"In small-town Minnesota in the 1970s, it's the tail-end of the age of peace and love, but 19-year-old Cash Blackbear isn't feeling it. Bored by freshman English 101 and even less interested in the increasingly popular American Indian Movement, all she wants is to play pool, learn judo, chain-smoke, and be left alone. But then one of Cash's classmates vanishes without a trace, and Cash can't stop dreaming about terrified girls begging for help. Plus, she has an unexpected houseguest: a brother she didn't know existed has moved into her living room, and he's having violent Vietnam flashbacks that Cash doesn't know how to handle. When Sheriff Wheaton, the man responsible for rescuing Cash from foster care, asks for Cash's help with the case of the missing girl, she must overcome her apprehension about leaving her hometown . . . along with her rule never to get in somebody else's car. Although Cash has been in big trouble before, this might just be her biggest trouble yet. Cash is whip-smart and tough-talking, as brave as she is vulnerable. Surrounded by a colorful cast of characters ranging from ditzy hippies to aggressive drunkards, and constantly being underestimated by the white administrators in charge of her day-to-day college existence, Cash must navigate not only being a Native American teenager living on her own for the first time-but also what responsibility she has to the other people in her life. Written in wry, fast-moving prose, Girl Gone Missing paints a vivid portrait of the 1970s and speaks to a powerful truth about the treatment of Native women and girls in America"--